Nurturing infants with music. (1st June 2019) - Trehub, Sandra E.
Primary caregivers throughout the world provide infants with life-sustaining care such as nutrition and protection from harm as well as life-enhancing care such as affection, contingent responsiveness and mentoring of various kinds. They nurture infants musically by means of one-on-one (i.e. infant-directed) singing accompanied by movement in some cultures and by visual gestures in others. Such singing, which is acoustically and visually distinct from solitary (i.e. self-directed) singing, is effective in engaging infants and regulating their mood and arousal. The repetition and stereotypy of caregivers' performances contribute to their memorability and dyadic significance. Caregivers' singing also influences infants' social engagement more generally. Once infants become singers, their songs play an important role in social interaction and emotional self-regulation. Although caregivers sing to infants with playful or soothing intentions, their performances highlight the temporal and melodic structure of the music. In sum, caregivers lay the foundation for a lifelong musical journey.